The Definition and Similar Constructs of Gratitude: A Critical Review - Subramanian, Bala R; Thakur, Munish; Chalil, Gloryson (Psychology Hub, 2022)
Despite the interest shown in the concept of gratitude over the last decade, there is no agreement on its definition and underlying dimensions. This paper provides a critical review of the definitions of gratitude and other similar constructs. A total of 22 definitions for gratitude were identified. The identified definitions were analyzed against each other for their commonality and differences. After highlighting the lacunae, lack of consensus, and overlap among the available definitions of gratitude, this paper differentiates gratitude from other similar constructs.